2014
DOI: 10.1002/ece3.1000
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of capture probabilities using generalized estimating equations and mixed effects approaches

Abstract: Modeling individual heterogeneity in capture probabilities has been one of the most challenging tasks in capture–recapture studies. Heterogeneity in capture probabilities can be modeled as a function of individual covariates, but correlation structure among capture occasions should be taking into account. A proposed generalized estimating equations (GEE) and generalized linear mixed modeling (GLMM) approaches can be used to estimate capture probabilities and population size for capture–recapture closed populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…) or in combination with radio‐telemetry data (Schwarz, Cope & Fratton ); new model fitting technology in an MCMC framework for addressing individual covariates (Bonner & Schofield ); fitting temporally varying individual covariates in hierarchical nest survival models (Converse et al . ); using posterior predictive checking as an aid to model selection (Chambert, Rotella & Higgs ); using generalized estimating equations as an alternative to Bayesian approaches to model heterogeneity in catchability (Akanda & Alpizar‐Jara ); using hidden Markov models to expand the toolbox for mark–recapture modelling (Choquet, Béchet & Guédon ); approaches for integrating memory models with mark–recapture modelling (Cole et al . ); and methods to deal with incompletely read marks in mark‐resighting studies (McClintock et al .…”
Section: Overview Of the 2013 Conference Proceedingsmentioning
confidence: 99%
“…) or in combination with radio‐telemetry data (Schwarz, Cope & Fratton ); new model fitting technology in an MCMC framework for addressing individual covariates (Bonner & Schofield ); fitting temporally varying individual covariates in hierarchical nest survival models (Converse et al . ); using posterior predictive checking as an aid to model selection (Chambert, Rotella & Higgs ); using generalized estimating equations as an alternative to Bayesian approaches to model heterogeneity in catchability (Akanda & Alpizar‐Jara ); using hidden Markov models to expand the toolbox for mark–recapture modelling (Choquet, Béchet & Guédon ); approaches for integrating memory models with mark–recapture modelling (Cole et al . ); and methods to deal with incompletely read marks in mark‐resighting studies (McClintock et al .…”
Section: Overview Of the 2013 Conference Proceedingsmentioning
confidence: 99%
“…This discussion is still ongoing, also in ecology (Fieberg et al . , ; Koper & Manseau ; Akanda & Alpizar‐Jara ).…”
Section: Introductionmentioning
confidence: 99%
“…After it became viable to fit conditional models to complex and large data sets, a long discussion ensued in the statistical literature, whether to choose a conditional or a marginal model (Neuhaus, Kalbfleisch & Hauck 1991;Lindsey & Lambert 1998;Heagerty & Zeger 2000;Diggle et al 2002;Lee & Nelder 2004). This discussion is still ongoing, also in ecology (Fieberg et al 2009(Fieberg et al , 2010Koper & Manseau 2009;Akanda & Alpizar-Jara 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akanda & Alpizar-Jara (2014a) proposed a generalized estimating equations (GEE) approach which accounts for individual heterogeneity and dependency among capture occasions, but their approach mainly focused on the M bh model. They also showed that the performance of the GEE approach is better than the mixed effects approach considering the closed population capture-recapture model, M h (Akanda & Alpizar-Jara 2014b).…”
mentioning
confidence: 99%